Identification and Expression Analysis of GRAS Transcription Factor Genes Involved in the Control of Arbuscular Mycorrhizal Development in Tomato - Ho-Plágaro, Tania; Molinero-Rosales, Nuria; Fariña Flores, David; Villena Díaz, Miriam; García-Garrido, José Manuel (Frontiers in Plant Science, 2019)
The formation and functioning of arbuscular mycorrhizal (AM) symbiosis are complex and tightly regulated processes. Transcriptional regulation mechanisms have been reported to mediate gene expression changes closely associated with arbuscule formation, where nutrients move between the plant and fungus. Numerous genes encoding transcription factors (TFs), with those belonging to the GRAS family being of particular importance, are induced upon mycorrhization. In this study, a screening for candidate transcription factor genes differentially regulated in AM tomato roots showed that more than 30% of known GRAS tomato genes are up-regulated upon mycorrhization. Some AM-upregulated GRAS genes were identified as encoding for transcription factors which are putative orthologs of previously identified regulators of mycorrhization in other plant species. The symbiotic role played by other newly identified AM-upregulated GRAS genes remains unknown. Preliminary results on the involvement of tomato SlGRAS18, SlGRAS38 and SlGRAS43 from the SCL3, SCL32 and SCR clades, respectively, in mycorrhization are presented. All three showed high transcript levels in the late stages of mycorrhization, and the analysis of promoter activity demonstrated that SlGRAS18 and SlGRAS43 are significantly induced in cells containing arbuscules. When SlGRAS18 and SlGRAS38 genes were silenced using RNA interference in hairy root composite tomato plants, a delay in mycorrhizal infection was observed, while an increase in mycorrhizal colonization was observed in SlGRAS43 RNAi roots. The possible mode of action of these TFs during mycorrhization is discussed, with a particular emphasis on the potential involvement of the SHR/SCR/SCL3 module of GRAS TFs in the regulation of gibberellin signaling during mycorrhization, which is analogous to other plant developmental processes